2006
DOI: 10.1063/1.2357638
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, and electrical properties of (Zn,Al)O films over a wide range of compositions

Abstract: ͑Zn,Al͒O thin films have been prepared by a dc reactive magnetron sputtering system with the Al contents in a wide range of 0 -50 at. %. The structural, optical, and electrical properties of ͑Zn,Al͒O films were detailedly and systematically studied. The amount of Al in the film was nearly the same as, but often lower than, that in the sputtering target. The growth rate of films monotonically decreased as the Al content increased. In a low Al content region ͑Ͻ10 at. % ͒, Al-doped ZnO ͑AZO͒ thin films could be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
181
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(201 citation statements)
references
References 85 publications
17
181
3
Order By: Relevance
“…Thus the resistivity will increase with Y dopant concentration above a certain threshold (0.10 at%), accompanied by the reduction of crystal domain size. Similar observations were reported for Al and Ga doped ZnO [46,47].…”
Section: Optical and Electrical Propertiessupporting
confidence: 78%
“…Thus the resistivity will increase with Y dopant concentration above a certain threshold (0.10 at%), accompanied by the reduction of crystal domain size. Similar observations were reported for Al and Ga doped ZnO [46,47].…”
Section: Optical and Electrical Propertiessupporting
confidence: 78%
“…Two strong peaks in the ranges of 34.51°to 34.71°(ICSD 98-004-0986) and 37.5°t o 37.7°(ICSD 98-002-6165) were observed which can be indexed to the ZnO (002) plane and a-plane sapphire, respectively. High intensity of the ZnO (002) peak simply indicates that the preferable growth orientation of ZnO structures is along the c-axis [39]. It is confirmed that the values of full width at half maximum (FWHM) determined from the ZnO (002) diffraction peak of the hydrothermally grown layers are similar as compared to the corresponding CVD ZnO seeds.…”
Section: Methodssupporting
confidence: 65%
“…Among them, V Zn is probably the most relevant defect, since it has the lowest formation energy among native point defects in n-type ZnO [1] and is commonly found in bulk and nanostructured materials [4][5][6][7][8]. V Zn is also suggested to be the origin of the observed n-type doping limit in ZnO [9,10] by forming complexes with donors leading to their compensation [11][12][13]. Therefore, it is crucial to understand the formation of intrinsic defects, especially V Zn , and their interaction with extrinsically important impurities such as shallow dopants in ZnO, which remains far from complete.…”
mentioning
confidence: 99%